PENGARUH GROWTH OPPORTUNITY, NET WORKING CAPITAL DAN CAPITAL EXPENDITURE TERHADAP CASH HOLDING - Jeshineta Angeline Hengsaputri, Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to determine the effect of growth opportunity, net working capital and capital expenditure to the cash holding in manufacturing companies that listed in Indonesia Stock Exchange for the period of 2016-2018. The hypothesis was examined using multiple regression analysis and processed with Eviews 9. From the results of research that has been done, it can be concluded that net working capital show a negative and significant relation with cash holding. However insignificant relationship was found between growth opportunity and capital expenditure with cash holding.